Antiviral mode of action of Lactobacillus plantarum YML009 on Influenza virus H1N1 (Bangladesh Journal of Pharmacology, 2015)
The development of resistance against antiviral agents has augmented a threat to public health sector. Consequently there is an expanding demand for the development of unconventional antiviral agents that could efficiently replace the existent in-use drugs. The probiotic strains of lactic acid bacteria (LAB) have earned the status of being efficient, economical and safe 'nutraceutical' in health care armamentarium. A total of 2272 LAB strains were screened against H1N1 virus. The isolate YML009 displayed a pronounced antiviral activity. Sequencing and biochemical assays identified the isolate as Lactoballius plantarum which, exhibited resistance to the damage caused by the acidic conditions such as gastric juice and 5% bile salt. The anti-H1N1 activity of the strain was confirmed by hemagglutination assay and was found to display enhanced efficacy in comparison to the commercially available antiviral drug. This is a primary report on anti-influenza activity of a bacterium L. plantarum YML009.